Can Taxes Help Ensure a Fair Globalization? - Langot, Francois; Merola, Rossana; Oh, Samil (World Bank, Washington, DC, 2019)
This paper analyzes whether taxation can be successfully used to reduce the incidence of labor informality and achieve higher equality in a globalized economy. To this purpose, it develops a two-area model: a developed country and an emerging country. The two areas differ according to the size of the informal sector, which is characterized by a more flexible labor market and lower productivity. To illustrate the potential role of taxation in achieving a more fair income distribution, the paper introduces a trade shock to simulate the effects of trade liberalization. Trade expansion has often been blamed for leading to an expansion of the informal sector and a widening of wage income disparities. In this context, the paper analyzes whether a budget-neutral tax reform -- switching the tax burden from payroll taxes paid by firms operating in the formal sector to a consumption tax -- can mitigate possible adverse effects of trade liberalization and support labor formalization. The effects of taxation are seen in the context of the trade-offs between growth, labor formality and equity. The analysis suggests that small improvements in formalization, resulting from the tax reform, come at the cost of widening income inequality. To reduce the incidence of low-quality jobs, tax policy interventions should go hand in hand with more effective social protection systems and labor laws.